Socioeconomic and ethnic inequalities increase the risk of type 2 diabetes: an analysis of NHS health check attendees in Birmingham - Au-Yeung, Chung Him; Ellis, David; Dallaway, Alexander; Riley, Jenny; Varney, Justin; Howell-Jones, Rebecca (Frontiers in Public Health, 2024)
IntroductionBirmingham has a significantly higher type-II diabetes prevalence than the national average. This study aimed to investigate the association of socioeconomic deprivation and ethnicity on the risk of diabetes in Birmingham.MethodsData were included from 108,514 NHS Health Checks conducted in Birmingham between 2018 and 2023. Attributable fraction and multinomial logistic regression were used to estimate the number of events avoidable and the prevalence odds ratios (POR) of determinants respectively.ResultsAttributable fraction analysis estimated that 64% of diabetes and 44% of pre-diabetes cases could be attributed to socioeconomic deprivation. Specifically, if Asian attendees in the least deprived areas had the same risk as White individuals in the least deprived areas, there would have been 1,056 fewer cases of diabetes and 2,226 fewer cases of pre-diabetes. Diabetes was significantly associated with Asian ethnicity (POR = 5.43, p < 0.001), Black ethnicity (POR = 3.15, p < 0.001) and Mixed ethnicity (POR = 2.79, p < 0.001). Pre-diabetes was also significantly associated with Asian ethnicity (POR = 3.06, p < 0.001), Black ethnicity (POR = 2.70, p < 0.001) and Mixed ethnicity (POR = 2.21, p < 0.001). The interaction effects between ethnicity and deprivation posed a greater risk of diabetes, especially for Asian attendees in the first (POR = 9.34, p < 0.001) and second (POR = 6.24, p < 0.001) most deprived quintiles.DiscussionThe present findings demonstrate the association of ethnicity and socioeconomic deprivation on the risk of diabetes and pre-diabetes. It underscores the necessity for targeted interventions and policies to address these inequalities.